2009 30th IEEE Real-Time Systems Symposium 2009
DOI: 10.1109/rtss.2009.11
|View full text |Cite
|
Sign up to set email alerts
|

New Response Time Bounds for Fixed Priority Multiprocessor Scheduling

Abstract: Recently, there have been several promising techniques developed for schedulability analysis and response time analysis for multiprocessor systems based on over-approximation. This paper contains two contributions. First, to improve the analysis precision, we apply Baruah's window analysis framework [6] to response time analysis for sporadic tasks on multiprocessor systems where the deadlines of tasks are within their periods. The crucial observation is that for global fixed priority scheduling, a response tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
212
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(216 citation statements)
references
References 14 publications
(24 reference statements)
4
212
0
Order By: Relevance
“…Bertogna and Cirinei (2007) adapted this approach to iteratively compute an upper bound on the response time of each task, using the upper bound response times of other tasks to limit the amount of interference considered. Guan et al (2009) extended the response time analysis of Bertogna and Cirinei (2007) for global FP scheduling, using ideas from Baruah (2007). Burns (2009, 2010a) showed that priority assignment is fundamental to the effectiveness of global FP scheduling.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Bertogna and Cirinei (2007) adapted this approach to iteratively compute an upper bound on the response time of each task, using the upper bound response times of other tasks to limit the amount of interference considered. Guan et al (2009) extended the response time analysis of Bertogna and Cirinei (2007) for global FP scheduling, using ideas from Baruah (2007). Burns (2009, 2010a) showed that priority assignment is fundamental to the effectiveness of global FP scheduling.…”
Section: Related Workmentioning
confidence: 99%
“…Burns (2009, 2010a) showed that priority assignment is fundamental to the effectiveness of global FP scheduling. They proved that the optimal priority assignment algorithm of Audsley (1991Audsley ( , 2001) is applicable to some of the sufficient tests developed for global FP scheduling, including the simple response time test of Andersson and Jonsson (2000) and the deadline-based test of Bertogna et al (2009), but not to others such as the response time tests of Bertogna and Cirinei (2007), and Guan et al (2009). Leung (1989) considered global Least Laxity First (LLF), referred to in that paper as the Slack Time algorithm.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…With the emergence of multicore processors, there is a reviving interest in the multiprocessor real-time scheduling problem and many results have been reported recently (Andersson et al 2008;Baruah and Baker 2008;Davis and Burns 2009a;Devi and Anderson 2005;Guan et al 2009Guan et al , 2010Kato and Yamasaki 2007;Levin et al 2010).…”
Section: Introductionmentioning
confidence: 99%